Theoretical Foundations of Multiple Intelligences and the Treatment of Environmental Awareness in Students - Abad Abad, Lenin Yung Vang (2023)
he present research is titled Theoretical Foundations of Multiple Intelligences and the Treatment of Environmental Awareness in Students, with the main objective of analyzing the potential application of the theoretical principles of multiple intelligences in the promotion of environmental awareness among students. For this, a qualitative methodology was developed in which a bibliographic review was carried out in different databases, initially finding 98 articles, proceeding to a discriminatory selection of them and finally managing to identify 45 articles which were used to obtain the data of this work. The results found showed that for the first variable referring to multiple intelligences it was identifiedin approximately 27% of the documents examined, while versatility was found in around 40%. On the other hand, the applications and uses were located in a percentage of 33% in the documents reviewed, in the same way the strategies for the treatment of environmental care, the articles that address these environmental strategies revealed that 24% exhibit innovative features, a 18% show flexibility, 24% have a critical approach, and 33% adopt a prospective and perspective orientation. Finally, it was possible to specify that the use of multiple intelligence enhances student learning, and even more so when they are aimed at developing knowledge and skills in caring for the environment.